Xanthones from garcinia eugenifolia / M.Taher, Muhammad Sum Idris, Dayar Arbain - 174651 M. Taher; Muhammad Sum Idris; Dayar Arbain; Malaysia National Natural Product Seminar (ke 16 : 1999 : USM, Pulau Pinang)
42